Agglomeration Economies and Heterogeneity within Young Innovative Companies - Marina Van Geenhuizen (European Regional Science Association (ERSA), 2005)
This paper fits into a new trend in empirical studies on agglomeration economies paying explicit attention to heterogeneity within innovative companies. The paper represents micro-level research, and is based on 21 in-depth case studies in a selected sample of young, innovative companies in the Netherlands. The selection criteria for sampling are derived from resource-based theory, e.g. age, size, corporate position, engaged in services or manufacturing industry. The selected sectors include mechatronics, biotechnology, ICT services and engineering services. In an attempt to identify causal factors and to identify different clusters of companies, we make use of rough set analysis, a method that typically fits small samples and qualitative data. Our research focuses on the importance perceived by company managers of a range of agglomeration advantages for the functioning of the company and on the perceived space in which the company could function satisfactorily. Based on our empirical explorations and given the theoretical positions of the selected case-studies, we arrive at the following findings (1) there is a divide of young, innovative companies into two, namely those facing a high level of importance (in large cities), and those facing a limited importance. In addition, network-based companies that outsource most of their activities to other companies may be facing no importance at all, potentially representing a third category; (2) the strongest factor influencing importance of agglomeration economies is corporate position, e.g. being a corporate spin-off or subsidiary (or not); (3) the spatial influence of agglomeration advantages tends to be broader than large cities only, but there are differences between the individual advantages, e.g. those working in a larger area of central cities, suburban places and medium-sized cities at larger distances, and those exclusively working in large cities or the largest city. Examples of the latter are a pool of young, internationally oriented labour force and direct access to the most advanced telecommunication infrastructure and services. The paper discusses the research design and the empirical outcomes and proposes various new hypotheses to be tested in large scale research.
Keywords: 330